2008
DOI: 10.1007/s10753-008-9062-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Producing γδ T Cells are Required for a Controlled Inflammatory Response after Bleomycin-induced Lung Injury

Abstract: Mouse gammadelta T cells produce IL-17 in response to lung injury and are required for an organized inflammatory response and epithelial repair. The lack of gammadelta T cells correlates with increased inflammation and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
95
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 61 publications
(75 reference statements)
8
95
1
Order By: Relevance
“…In a chronic B. subtilis infection, mice lacking ␥␦ T cells demonstrated an enhanced fibrotic phenotype 24 because of enhanced inflammation. In support of our study, Braun et al 36 recently showed that mice lacking ␥␦ T cells had slower epithelial repair in response to bleomycin treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a chronic B. subtilis infection, mice lacking ␥␦ T cells demonstrated an enhanced fibrotic phenotype 24 because of enhanced inflammation. In support of our study, Braun et al 36 recently showed that mice lacking ␥␦ T cells had slower epithelial repair in response to bleomycin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies 37,38 have shown that ␥␦ T cells promote epithelial repair in skin and intestine through the production of fibroblast growth factor 7, also known as keratinocyte growth factor. However, similar to other pulmonary injury models, 22,36 the current study did not detect any differences in keratinocyte growth factor between ␥␦ KO mice and WT mice (data not shown). However, cytokine and chemokine analysis of lung homogenate demonstrated that ␥␦ KO mice were deficient in the chemokines CXCL1, IL-6, G-CSF, and CXCL10.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with our results, gd T cells in the lungs of WT mice were found to predominantly produce IL-17, and the amount of hydroxyproline in the lungs increased in gd T cell-deficient mice during BIPF (41). In contrast, in a recent study, IL-17A produced by CD4 + and gd + T cells promoted bleomycin and IL-1b-mediated pulmonary fibrosis (42).…”
Section: Discussionsupporting
confidence: 90%